THE GROWING THREAT OF CARBAPENEM AND CEPHALOSPORIN RESISTANCE: ANTIMICROBIAL RESISTANCE PATTERNS OF WHO PRIORITY PATHOGENS IN A TERTIARY CARE SETTING - Ali, Irshad; Safina Mufti,; Noreen Taj,; Ashfaq, Muhammad; Muhammad Junaid Hassan Sharif,; Qasim Khan,; Syed Mobasher Ali Abid, (Journal of Ayub Medical College Abbottabad, 2025)
Background: Antimicrobial resistance is an increasing global health issue with increased resistance to carbapenems and cephalosporins among WHO priority pathogens, particularly in low- and middle-income countries like Pakistan. The current study aimed to analyze the prevalence and resistance patterns of selected WHO Priority Pathogens at Saidu Teaching Hospital, SWAT, Pakistan.